THE LAST QUEEN OF GEORGIA MARIA - Imerlishvili, Ivane (European Scientific Journal, ESJ, 2014)
In the paper the fact of an assassination of General Lazarev (1766-1803) is discussed, which up to the present day according to the existing Georgian, Russian and European sources and according to the existing special literature in the Foreign languages, is prescribed to the last Queen of Georgia Maria (1768-1850) which is an inaccurate version and is based on an unfounded supposition. An assassination as if done by the last Queen of Georgia Maria, who was the wife of King Giorgi XII (1746-1800), does not coincide with an assumption of many Georgian, Russian and European scientists.